Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2527/jas.2013-7112
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing antioxidants to pigs fed diets high in oxidants: II. Effects on carcass characteristics, meat quality, and fatty acid profile1

Abstract: The study was conducted to determine effects of dietary supplementation with a blend of antioxidants (ethoxyquin and propyl gallate) on carcass characteristics, meat quality, and fatty acid profile in finishing pigs fed a diet high in oxidants. A total of 100 crossbred barrows (10.9±1.4 kg BW, 36±2 d of age) were randomly allotted to 5 diet treatments (5 replicate pens per treatment, 4 pigs per pen). Treatments included: 1) HO: high oxidant diet containing 5% oxidized soy oil and 10% PUFA source which contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
4
16
1
Order By: Relevance
“…In agreement with some previous studies in pigs (Lu et al, 2014b), an increment of liver weight and liver to BW ratio induced by oxidized oil was apparent in the present study. This increase resulted from the elevated absolute weight of the livers because dietary oxidized sunflower oil did not produce a significant effect on BW.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with some previous studies in pigs (Lu et al, 2014b), an increment of liver weight and liver to BW ratio induced by oxidized oil was apparent in the present study. This increase resulted from the elevated absolute weight of the livers because dietary oxidized sunflower oil did not produce a significant effect on BW.…”
Section: Discussionsupporting
confidence: 94%
“…A number of studies have shown that domestic animal production performance was depressed by dietary addition of oxidized lipids (Yue et al, 2011;Fontagné-Dicharry et al, 2014;Lu et al, 2014a and2014b;Rosero et al, 2015). The depression partly resulted from a reduced palatability of the rancid feed, leading to a lower feed intake .…”
Section: Discussionmentioning
confidence: 99%
“…) and also a trend toward higher muscle pH at 24 h postmortem (5.7 vs. 5.5) (Lu et al. ); however, there is no further information on the possible interaction effects with the selenium source.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in our study, muscle pH did not affect vitamin E concentration (Table 4). A direct association between muscle vitamin E and lower drip loss has been described (Ashgar et al 1991) and also a trend toward higher muscle pH at 24 h postmortem (5.7 vs. 5.5) (Lu et al 2014); however, there is no further information on the possible interaction effects with the selenium source.…”
Section: Tocopherol Accumulationmentioning
confidence: 99%
“…The SC diet was formulated to approximate a corn-soybeanbased diet typical of North American production conditions. Analyzed fatty acid profiles of the experimental diets and commercial PUFA source are presented in a companion paper (Lu et al, 2014). All experimental diets were fed on an ad libitum basis throughout the experiment.…”
Section: Animals and Experimental Designmentioning
confidence: 99%